International Capital Flows and World Output Gains - von Hagen, Jurgen (Institutional Knowledge at Singapore Management University, 2010)
We develop a two-country overlapping-generations model with domestic financial frictions and show that cross-country differences in financial development explain three recent patterns of international capital flows. In our model, domestic financial frictions distort the interest rates and production efficiency in the less financially developed country. Capital flows not only lead to cross-country resource reallocation, but also trigger within-country resource reallocation among firms. From the efficiency perspective, full capital mobility raises the world output higher than under international financial autarky. If the mobility of either financial capital or foreign direct investment is restricted, the world output may be lower.